Covalent Graphene-MOF Hybrids for High-Performance Asymmetric Supercapacitors - Jayaramulu, Kolleboyina; Horn, Michael; Schneemann, Andreas; Saini, Haneesh; Bakandritsos, Aristides; Ranc, Vaclav; Petr, Martin; Stavila, Vitalie; Narayana, Chandrabhas; Scheibe, Błażej; Kment, Štěpán; Otyepka, Michal; et al. (Advanced materials (Deerfield Beach, Fla.), 2021)
In this work, the covalent attachment of an amine functionalized metal-organic framework (UiO-66-NH2 = Zr6 O4 (OH)4 (bdc-NH2 )6 ; bdc-NH2 = 2-amino-1,4-benzenedicarboxylate) (UiO-Universitetet i Oslo) to the basal-plane of carboxylate functionalized graphene (graphene acid = GA) via amide bonds is reported. The resultant GA@UiO-66-NH2 hybrid displayed a large specific surface area, hierarchical pores and an interconnected conductive network. The electrochemical characterizations demonstrated that the hybrid GA@UiO-66-NH2 acts as an effective charge storing material with a capacitance of up to 651 F g-1 , significantly higher than traditional graphene-based materials. The results suggest that the amide linkage plays a key role in the formation of a π-conjugated structure, which facilitates charge transfer and consequently offers good capacitance and cycling stability. Furthermore, to realize the practical feasibility, an asymmetric supercapacitor using a GA@UiO-66-NH2 positive electrode with Ti3 C2 TX MXene as the opposing electrode has been constructed. The cell is able to deliver a power density of up to 16 kW kg-1 and an energy density of up to 73 Wh kg-1 , which are comparable to several commercial devices such as Pb-acid and Ni/MH batteries. Under an intermediate level of loading, the device retained 88% of its initial capacitance after 10 000 cycles.
Keywords: 2D materials; MXenes; covalent assemblies; metal-organic frameworks; asymmetric supercapacitors